USM PROFESSOR DATO' DR. JAFRI MALIN APPOINTED AS ADVISOR OF INTERNATIONAL YOUTH NEUROSCIENCE ASSOCIATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 December 2016 The Director and Founder of the Universiti Sains Malaysia (USM) Centre for Neuroscience Services and Research (P3Neuro), the first in Southeast Asia, Professor Dato' Dr. Jafri Malin bin Abdullah has been appointed as the Advisor of the International Youth Neuroscience Association (IYNA), based at the University of Maryland, Baltimore, USA.